Novel Two-Component System-Like Elements Reveal Functional Domains Associated with Restriction–Modification Systems and paraMORC ATPases in Bacteria. (10th February 2021) - Bellieny-Rabelo, Daniel; Pretorius, Willem J S; Moleleki, Lucy N
Abstract: Two-component systems (TCS) are important types of machinery allowing for efficient signal recognition and transmission in bacterial cells. The majority of TCSs utilized by bacteria is composed of a sensor histidine kinase (HK) and a cognate response regulator (RR). In the present study, we report two newly predicted protein domains—both to be included in the next release of the Pfam database: Response_reg_2 (PF19192) and HEF_HK (PF19191)—in bacteria which exhibit high structural similarity, respectively, with typical domains of RRs and HKs. Additionally, the genes encoding for the novel predicted domains exhibit a 91.6% linkage observed across 644 genomic regions recovered from 628 different bacterial strains. The remarkable adjacent colocalization between genes carrying Response_reg_2 and HEF_HK in addition to their conserved structural features, which are highly similar to those from well-known HKs and RRs, raises the possibility of Response_reg_2 and HEF_HK constituting a new TCS in bacteria. The genomic regions in which these predicted two-component systems-like are located additionally exhibit an overrepresented presence of restriction–modification (R–M) systems especially the type II R–M. Among these, there is a conspicuous presence of C-5 cytosine-specific DNA methylases which may indicate a functional association with the newly discovered domains. The solid presence of R–M systems and the presence of the GHKL family domain HATPase_c_3 across most of the HEF_HK-containing genes are also indicative that these genes are evolutionarily related to the paraMORC family of ATPases.